Threat Perception, Vision of Order, and the Logic of Changes in the US–Japan Alliance in the Post-Cold War Era - Yiming Zeng; Xiaodi Ye (Chinese Journal of International Review)
To explore the underlying logic behind the evolution of the US–Japan alliance in the post-Cold War era, this research constructs an explanatory framework that analyzes the alliance cohesion in security, economic, and political cooperation through threat perceptions and visions of order. It proposes a typology including four types of alliances: Drifting Alliance, Rules-Maintaining Alliance, Threat-Balancing Alliance, and Comprehensively Collaborative Alliance. In the Drifting Alliance, alliance cohesion is the lowest, as the differing threat perceptions and divergent visions of order between the United States and Japan resulted in deviating objectives and hindering cooperation; In the Rules-Maintaining Alliance, alliance cohesion is semi-strong. Despite differing threat perceptions, the United States and Japan share converging visions of order, allowing the US–Japan alliance to enhance economic and political cooperation, but impeding security cooperation. In the Threat-Balancing Alliance, alliance cohesion is medium. Their consistent threat perceptions and divergent visions of order strengthen imperative security cooperation to balance threats, but fail to reach a consensus on economic cooperation and political cooperation. In the Comprehensively Collaborative Alliance, alliance cohesion is the strongest. The United States and Japan share consistent threat perceptions and converging visions of order, resulting in the strengthening and mutual reinforcement of security, economic, and political cooperation.